Patintero comics - Castillo, Kai ([Kai Castillo], 2016)
"The match between the red flames and punks-ND is nearing its end. We will see hoe the red flames handles this game and who wins this round. On another note, the PH suns players return, creating a vital role in the floe of the story. Will this benefit the newly formed team?: or shatter their hopes and dreams of playing in the big league?" -- Provided by publisher